2017
DOI: 10.1111/een.12493
|View full text |Cite
|
Sign up to set email alerts
|

Biotic filtering and mass effects in small shrub patches: is arthropod community structure predictable based on the quality of the vegetation?

Abstract: 1. Community assembly is affected by four processes: dispersal, filtering effects (selection), ecological drift and evolution. The role of filtering relative to dispersal and drift should decline with patch size, hampering possibilities to predict which organisms will be observed within small‐sized patches. However, vegetation structure is known to have a marked impact on species assemblages, and plant quality may act as a biotic filter. This challenges the assumption of unpredictable species assemblages in sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…We found shrubs decreased the functional richness difference component, which suggested that the functional homogenization is often linked to deterministic processes of environmental filtering (Si et al, 2016; Zhao et al, 2021). Shrubs functioning as habitats for nematode communities can limit the range of potential colonizers by favoring species with particular functional attributes (Cao et al, 2016; Lanta et al, 2018). Combined with the single functional traits and functional composition, shrubs increased body mass, C – P value, and proportions of omnivore and predator nematodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found shrubs decreased the functional richness difference component, which suggested that the functional homogenization is often linked to deterministic processes of environmental filtering (Si et al, 2016; Zhao et al, 2021). Shrubs functioning as habitats for nematode communities can limit the range of potential colonizers by favoring species with particular functional attributes (Cao et al, 2016; Lanta et al, 2018). Combined with the single functional traits and functional composition, shrubs increased body mass, C – P value, and proportions of omnivore and predator nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…Shrubs and its interactions with precipitation can potentially influence the processes behind community assembly, and therefore functional beta diversity. On the one hand, functioning as habitat for nematodes, shrubs can limit the range of potential colonizers by favoring or excluding species with particular functional attributes, decreasing nematode functional beta diversity (Lanta et al, 2018; Siegwart Collier & Mallik, 2010; Wardhaugh et al, 2012; Xiang et al, 2019). Moreover, shrubs trigger large shifts in soil heterogeneity that limit local species coexistence, decreasing functional richness differences and overall functional beta diversity of nematode communities (Albrecht et al, 2021; Chesson, 2000; Hao et al, 2021; Losapio et al, 2018; Schöb et al, 2013; Trentanovi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Shrub encroachment is an irreversible process with potential effects on the soil environmental heterogeneity and plant communities, thus affecting the beta diversity of soil communities (Hao et al , 2021). On the one hand, shrubs, which function as habitat for soil communities, could limit the range of potential colonizers by favoring or excluding species with particular functional attributes, which would directly decrease beta diversity of soil communities (Siegwart Collier & Mallik, 2010;Wardhaugh et al , 2012;Lanta et al , 2018;Xiang et al , 2019). On the other hand, shrub triggers large shifts in plant communities and soil environmental heterogeneity, indirectly affecting beta diversity of soil communities.…”
Section: Introductionmentioning
confidence: 99%
“…mass effects or spillover) 29 , 30 . In this case, high dispersal rates maintain species in sites with negative growth rates 31 and override the effects of local selection 8 , 18 , 30 , 32 .…”
Section: Introductionmentioning
confidence: 99%